Defense Without Inflation/Financing Defense (Book). - Simpson, Floyd R.; Cannon, Arthur M. (The Accounting Review, 1952)
Reviews two books. " Defense Without Inflation," by Albert G. Hart; "Financing Defense," by Albert G. Hart and E. Cary Brown.